The haunted cabin mystery. - Warner, Gertrude Chandler, 1890-1979. (Morton Grove, Ill : A. Whitman, 1996)
The Alden children travel on a Mississippi paddle-wheel steamer to visit an old family friend in his cabin near Hannibal, Missouri, and try to discover who is responsible for the mysterious activities near the house.
630
Accelerated Reader AR
Keywords: Mystery and detective stories -- Brothers and sisters -- Fiction; Boxcar children (fictitious characters) -- Orphans -- Juvenile fiction